Theresa May’s BBC Speech on Brexit Referendum: An Interpersonal Metafunction Analysis - Nur Rizky Alfiany Suaib (Journal of Education and Teaching (JET), 2022)
Interpersonal metafunction is one of three components of linguistic study within the Systemic Functional Linguistics framework (SFL). It is concerned with how language users express ideas in texts in order for their audience to perceive them. In regards to political discourse, this study aims to unravel what PM Theresa May tries to deliver to her audience. By examining the patterns of independent clauses in her BBC speech regarding Brexit referendum, it indicates the presence of declarative and/or statement sentences. There is clearly an exchange pattern between the speaker (Theresa May) and the targeted listener (British citizen). She planned the order of her speech, beginning with an explanation of the existing state of the United Kingdom and her new elevated position as Prime Minister, as a preamble to her theme speech, the Brexit referendum. By boosting her speech (using the finite 'will'), she explored her promise of a far better life for British citizens after leaving the EU, and in the final portion of her address, she maintained a strong demand (using the high modulation 'must') to realize her planned goal. This text analysis as a whole may provide extra insight into political speech language.